Removal of arsenic from aqueous solutions by sorption onto sewage sludge-based sorbent - Tavares, Daniela S. (2019)
This study aimed at evaluating and comparing the removal of arsenic from solutions by a low-cost waste-based sorbent, produced by pyrolysing sewage sludge under appropriate conditions, and by a commercially activated carbon. Batch sorption experiments were performed under isothermal conditions (20°C), in order to evaluate the effect of pH on the arsenic sorption kinetics and on the equilibrium sorption capacity of the materials under study. Kinetic data revealed that the arsenic sorption was faster onto the activated carbon than onto the pyrolysed sludge. The sorption process was well described by both the pseudo-first and pseudo-second-order kinetics equations for both materials. Changes in the initial solution pH have distinct effects on the removal of arsenic onto pyrolysed sludge and activated carbon. While for pyrolysed sludge, pH affects essentially the equilibrium time, for activated carbon it affects the sorption capacity. Equilibrium results were well described by both Freundlich and Langmuir isotherm models, although fittings corresponding to the Langmuir isotherm were slightly better. The Langmuir maximum sorption capacity determined for the pyrolysed sludge was 71 μg g−1, while for activated carbon was 229 μg g−1. Despite the relative lower capacity of the pyrolysed sludge, the considerable lower cost and the valorisation of the sludge may justify further research on its use for water decontamination.